Epistemic Modality in Miss Marple’s Language: From Assumption to Certainty in Agatha Christie’s Nemesis - Fauziah Rohayatien Husna; Almira Irwaniyanti Utami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
While epistemic modality has been examined across various discourse contexts—from political speeches to academic writing—its correlation with narrative development in detective fiction remains largely unexplored. The existing studies dominantly applied Systemic Functional Linguistics frameworks that position epistemic modality within interpersonal functions, so its semantic aspects in literary narratives are not discussed. To fill this gap, this study analyzes Epistemic Modality in Miss Marple’s language in Agatha Christie’s Nemesis (1971), with the research question of how changes in epistemic commitment are connected with narrative development. Employing a qualitative-descriptive approach, the research applies Palmer’s (2001) framework of epistemic modality, which categorizes into: epistemic possibility, epistemic probability, and epistemic certainty. Palmer’s framework is particularly suited to this study, as it examines epistemic modality at the level of propositional meaning, enabling a systematic analysis of how each degree of commitment shifts across the novel's 23 chapters. The data exclusively consist of Miss Marple’s utterances containing epistemic modal markers, collected through purposive reading and analyzed through identification, classification, and interpretation. The findings reveal that all degrees of epistemic commitment occur throughout the narrative, though the distribution varies across the investigation's stages. A gradual increase in epistemic commitment is observed, from tentative assumptions in the earlier chapters toward certainty based on reasoning in the final chapters, while lower degrees coexist with higher ones. This pattern demonstrates the layered and progressive nature of investigative reasoning. Therefore, these findings confirm that Epistemic Modality in Miss Marple’s language functions as a semantic mechanism that reflects Nemesis's narrative arc, contributing to literary linguistics by demonstrating how Palmer’s semantic framework can reveal the relationship between characters’ epistemic language and narrative development. by illustrating how a character’s epistemic language can reflect narrative development.